Concrete mix transportation modelling - Koźniewski, Edwin; Orłowski, Zygmunt (Journal of Civil Engineering and Management, 2003)
The paper presents the simulation model of concrete mix transportation process in the system – batching centre – a number of construction sites. An essential part of the analysed model is a multi-phase system of queues which emerge in concrete transportation characterised by: waiting time for loading, waiting for discharge, the distances from the plant to construction sites, the number and type of truck mixers used, the types of transport means for on-site deliveries, transportation costs. The paper also includes an example solved with a computer program designed on the basis of an algorithm formulated in the model.First Published Online: 26 Jul 2012